Persepsi Publik Terhadap Perpindahan Ibu Kota Ke IKN Berdasarkan Analisis Sentimen X Menggunakan Naïve Bayes Classifier - Fauzan; Wiwik Kusrini; Fathurrahmani (P3M Politeknik Negeri Banjarmasin, 2025)
The relocation of Indonesia’s capital city from Jakarta to Nusantara (IKN) has become a topic that generates various public reactions. These opinions are largely expressed through the social media platform X (formerly Twitter), making it an important data source for analyzing public sentiment. This study aims to apply the Naïve Bayes Classifier method to analyze public sentiment toward the relocation of IKN and to evaluate its accuracy using a Confusion Matrix. The data were collected through a web crawling process on the X platform using the keyword